Comparison of e-government acceleration in five regions: Case studies following the issuance of Presidential Regulation 95/2018 - Fahrul Muzaqqi; Hari Fitrianto (Masyarakat, Kebudayaan dan Politik, 2023)
One year following the issuance of Presidential Regulation Number 95 of 2018 (Perpres 95/2018), all local governments are competing to implement an electronic-based government system (SPBE/e-Government/eGov). This study, which was conducted in the 2021-2022 period, aimed to examine e-Gov planning and then compare its practice in the five regions (Surabaya, Banyuwangi, Sleman, Gresik, and Kulon Progo) focusing on the results of the 2019 SPBE evaluation and the availability of a legal umbrella in the form of Regent/Mayor Regulations governing the implementation of e-Gov. Starting with the e-Gov theoretical framework, this study used a qualitative-descriptive method with internet secondary data, library research, SPBE index review, and supporting documents. The results of this study are: (a) there are four phases of e-Gov planning: automation, optimization, reengineering, and transformation. The acceleration of the implementation of the SPBE includes the integration of planning, budgeting, procurement, personnel data, archives, public complaints, and data centers; (b) responsively, the five regions compared in this study already have a legal umbrella in the form of a Regent/Mayor Regulations one year following the issuance of Presidential Decree 95/2018; (c) The SPBE service domain is a reliable indicator among the five regions, while the SPBE governance and policy domain displays different dynamics among them. This study concludes that Indonesia’s performance in e-Gov practice is still not convincing among other countries globally and recommends more innovative implementation of e-Gov from authorities (government) without neglecting periodic evaluations.